Chinese Indonesians and regime change - Dieleman, Marleen; Koning, Juliette; Post, Peter, 1953- (Chinese overseas ;, 2011)
The existing literature on Chinese Indonesians has so far tended to take an approach of either victimization and marginalization or a focus on elite businessmen and their economic influence. This volume takes a different perspective. The Chinese in Indonesia were not only innocent victims of history, but were simultaneously active agents of change. Chinese Indonesians from different walks of life played an active role in shaping society during regime changes and found creative and constructive ways to deal with situations of adversity. This book demonstrates that regime changes in Indonesia did not only pose threats of violence, but also offered opportunities that induced "agency" on the part of Chinese Indonesians to shape their own destinies and that of the country.